Exchange rate misalignments, growth, and institutions - Jaromír Baxa; Michal Paulus (Charles University in Prague, Institute of Economic Studies (IES), 2020)
In this paper, we revisit the relationship between economic growth and exchange rate misalignments, especially undervaluations. In particular, we ask which countries benefit from undervaluations at most, and whether the impact of undervaluations on growth depends on institutional quality as suggested in previous literature. First, we separate countries into groups according to their institutional quality using the cluster analysis. Then, we estimate the relationship between growth and exchange rate misalignment while allowing for variation in coefficients across these clusters. Our results confirm the positive relationship between undervaluation and growth, and this relationship is the highest for countries with the highest quality of institutions rather than with a poor level of institutional quality. Therefore, our results reconcile the importance of good institutions and do not support the hopes that the countries can compensate for the poor institutional quality via undervaluation of currencies successfully.
Keywords: F43; F31; O43; 330; exchange rate misalignments; undervaluation; economic growth; institutions; corruption